Kinerja Dinas Pengendalian Penduduk, Keluarga Berencana dan Pemberdayaan Perempuan, Perlindungan Anak (DP2KBP3A) dalam Menangani Kasus Kekerasan pada Perempuan dan Anak di Kabupaten Pandeglang, Banten Tahun 2020 - Rahmi Andini Syamsuddin; Lisdawati Lisdawati (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2020)
The primary purpose of this study is to find out about the performance of DP2KBP3A and to identify the impact factors of the performance of DP2KBP3A in handling women and child abuse in Pandeglang. The theoretical concept used is the performance theory, and the indicators are productivity, service quality, responsiveness, responsibility, and accountability. This study uses a descriptive qualitative method, the selection of informants using the Purposive sampling technique—the technique of collecting data through interviews, observation, and documentation. The results of this study indicate that the performance of DP2KBP3A in Pandeglang has not been effective. Some factors that impact the performance are budget, socialization, and communication. It is better for DP2KBP3A to improve the performance in management further starting from productivity, service quality, responsiveness, responsibility, and accountability, and need to prepare permanent staff who can stand by at any time providing services according to procedures.